MISI CYBERPHYSICAL SEBAGAI SARANA PENGINJILAN EFEKTIF TERHADAP DIGITAL NATIVES DI ERA SOCIETY 5.0 - Normando Justine; Shekinah Theofany (Jurnal Matetes STT Ebenhaezer, 2023)
This research uses a qualitative descriptive method to understand the phenomenon of digital natives, Society 5.0, and the role of church missions in cyberphysical evangelism in the Society 5.0 era. Data was obtained from books, journals and websites with integrity. The analysis results show that in Society 5.0, churches have the opportunity to play a role in more effective evangelism to digital natives who are increasingly connected digitally. Churches need to adapt to technological developments, use cyberphysicalmissions wisely, and ensure that online communications are in line with Christian values. The use of technologies such as VR, AR, and AI can be relevant tools to evangelize digital natives, taking into account the characteristics of those who like the instant, individualistic, and creative. A focus on online communities and social media can also increase the effectiveness of evangelism. In Society 5.0, churches need to take an active role in using technology for effective evangelistic purposes.